Social participation and media democratization: ways to expand the rights to communication and health - Pâmela Pinto (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2021)
The book Right to Communication and Health discusses the interrelationship between these two human rights and their reflection on the exercise of citizenship. The authors look back on the connection between these two fields, especially from the mobilizations that originated the Brazilian Unified Health System (SUS) and the regulatory scenario (broadcasting and the Internet) in the country. The democratization of Brazilian communications and the expansion of social participation were described as central elements for the configuration of a democratic society. The work advocates for communication as a public good that should be collectively shared.